2020
DOI: 10.1007/s00248-020-01498-6
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Resistant Heterotrophic Ammonium and Nitrite-Removing Bacteria Improve Aquaculture Conditions of Rainbow Trout (Oncorhynchus mykiss)

Abstract: The aim of this study was isolation and characterization of heterotrophic bacteria capable of ammonium and nitrite removal at 15°C (optimal temperature for growing rainbow trout Oncorhynchus mykiss). Environmental isolates were grown in liquid media containing ammonium or nitrite, and best strains in terms of growth and ammonium or nitrite removal were identified via 16S rRNA sequencing. Dyadobacter sp. (no. 68) and Janthinobacterium sp. (no. 100) were selected for optimal adaptation to growth at 15°C and best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“… 33 Excessive inorganic N compounds in non-RCFP ( Figures S1 C–S1F and S2B-C) are adverse for aquatic animals. 12 , 30 , 34 Collectively, these findings indicated that RCFP has higher N assimilation and N contamination removal abilities.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“… 33 Excessive inorganic N compounds in non-RCFP ( Figures S1 C–S1F and S2B-C) are adverse for aquatic animals. 12 , 30 , 34 Collectively, these findings indicated that RCFP has higher N assimilation and N contamination removal abilities.…”
Section: Resultsmentioning
confidence: 74%
“… 45 Previous research has reported that accumulated inorganic nitrogen compounds at the highest stocking density inhibit innate immunity and induce oxidative stress in red seabream, 30 whereas the high levels of ammonium and nitrite in non-RCFP ( Figures S1 D–S1E, S2 B, and S2C) might impair the immune system of aquatic animals, making them more susceptible to infections, as well as affecting their growth and yield. 34 , 46 , 47 Moreover, previous studies have also reported that non-RCFP has higher level of antibiotics compared with RCFP, 26 such as tetracycline, which may increase nitrous oxide emissions. 48 In addition, nitrous oxide is also an important greenhouse gas with approximately 300 times global warming potential compared to carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…Marinobacter strain NNA5 had zero N 2 O emissions in the same way as strain HS2 [ 28 ]. Nitrite is harmful to water organisms, so it is critical to isolate strains that have no nitrite accumulation in aquaculture sewage [ 37 ]. In contrast, the final product of ammonia nitrogen removal by Halomonas salifodinae Y5 is nitrite nitrogen [ 27 ], while strain HS2 would not influence the quality of the water during the removal of ammonia nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Fish intestinal microbes plays a crucial role in improving nutrient utilization, regulating lipid catabolism, transport, and storage, and preventing polyunsaturated fatty acid peroxidation (Semova et al 2012;Chen et al 2015). 16S rRNA gene sequencing technology can re ect the dynamic changes in micro ora intuitively and has been widely used in the study of sh intestinal microbes (Neissi et al 2020;Webster et al 2021).…”
Section: Introductionmentioning
confidence: 99%